Puerto Ricans in the Empire : Tobacco Growers and U.S. Colonialism - Levy, Teresita A. (Book collections on Project MUSE., 2015)
Most studies of Puerto Rico's relations with the United States have focused on the sugar industry, recounting a tale of victimization and imperial abuse driven by the interests of U.S. sugar companies. But inPuerto Ricans in the Empire, Teresita A. Levy looks at a different agricultural sector, tobacco growing, and tells a story in which Puerto Ricans challenged U.S. officials and fought successfully for legislation that benefited the island. Levy describes how small-scale, politically involved, independent landowners grew most of the tobacco in Puerto Rico. She shows how, to gain access to pol.